Obstetric anal sphincter injury: a follow-up questionnaire study on longer-term outcomes. Issue 10 (October 2016) - Cornelisse, Simone; Arendsen, Linda; Kuijk, Sander; Kluivers, Kirsten; Dillen, Jeroen; Weemhoff, Mirjam
Abstract Introduction and hypothesis Obstetric anal sphincter injuries (OASIS) contribute significantly to the development of anal incontinence (AI) in women. The aim of this study was to establish the incidence of AI after OASIS and to study the influence on the quality of life (QoL) in patients with OASIS. Methods This cohort study, with prospective case-control follow-up, involves women who were treated for OASIS between 2005 and 2012 in two academic medical centers in The Netherlands. Three hundred and thirteen patients and 780 controls were invited to complete a validated questionnaire (Defecation Distress Inventory, Wexner Incontinence Score, and Fecal Instrument Quality of Life) regarding symptoms and bother of AI subsequent and QoL after delivery. The main outcome measures were the presence of AI and the impact on QoL. Results The questionnaire was completed by 141 patients and 194 controls. Mean follow-up was 4 years (range 1–9 years) in both groups. In the patient group, 55 women (39 %) reported AI symptoms compared with 38 women (20 %) in the control group (odds ratio 2.7, 95 % confidence interval 1.66–4.47, p < 0.01). In women who experienced symptoms of AI as very bothersome, QoL was affected in 14 (82.0 %) patients and three (33.5 %) controls (p = 0.012). Conclusions In this study, women with OASIS had a more than doubled risk of longer-term bothersome symptoms of AI compared with controls. Symptoms were experienced as bothersome and as having an influence on QoL.